Population and economic training of the reserve of sustainable development of Tupé in the community our Nossa Senhora do Livramento – Manaus/AM (Research, Society and Development, 2022)
The general objective of the research is to describe the population, economic and social aspects of the Community of Our Lady of Livramento located in the Sustainable Development Reserve of Tupé (RDS) located in Manaus/AM. The research is an exploratory study, of descriptive character, with a qualiquantitative approach carried out through the application of a questionnaire with 252 residents of that locality, the questions were constructed to know the population profile, economic characteristics and social conditions. The population profile indicates that 64% declare themselves women, 35.71% of the participants indicate to be more ≥ 61 years of age, 90.87% declare themselves brown, 42.06% said they have naturalness in the city of Manaus, and 35.32% live in the locality between 1 and 10 years. As for the economic characteristics, it is pointed out that 78.57% do not perform paid activity, but 51.23% exercise some economic activity with agricultural production, 59.52% have in their family group one or two people with fixed work, 63.10% said they had a family income between R$ 1,212.00 and R$2,424.00. Finally, the housing condition of the participants indicates that 66.67% have their own paid housing, 23.02% live in a house with 4 to 6 residents. In short, the analysis of the social, economic and population organization of the Community Of Our Lady of Deliverance, covering the knowledge about this traditional population, is extremely important from the point of view of the use and environmental conservation and development of this unit, since it is fundamental to know the socioeconomic potentials of this unit, because it contributes to the quality of life of this population.